Prediction of the Sex-Associated Genomic Region in Tunas (Thunnus Fishes) - Yoji Nakamura; Kentaro Higuchi; Kazunori Kumon; Motoshige Yasuike; Toshinori Takashi; Koichiro Gen; Atushi Fujiwara (International Journal of Genomics)
Fish species have a variety of sex determination systems. Tunas (genus Thunnus) have an XY genetic sex determination system. However, the Y chromosome or responsible locus has not yet been identified in males. In a previous study, a female genome of Pacific bluefin tuna (T. orientalis) was sequenced, and candidates for sex-associated DNA polymorphisms were identified by a genome-wide association study using resequencing data. In the present study, we sequenced a male genome of Pacific bluefin tuna by long-read and linked-read sequencing technologies and explored male-specific loci through a comparison with the female genome. As a result, we found a unique region carrying the male-specific haplotype, where a homolog of estrogen sulfotransferase gene was predicted to be encoded. The genome-wide mapping of previously resequenced data indicated that, among the functionally annotated genes, only this gene, named sult1st6y, was paternally inherited in the males of Pacific bluefin tuna. We reviewed the RNA-seq data of southern bluefin tuna (T. maccoyii) in the public database and found that sult1st6y of southern bluefin tuna was expressed in all male testes, but absent or suppressed in the female ovary. Since estrogen sulfotransferase is responsible for the inactivation of estrogens, it is reasonable to assume that the expression of sult1st6y in gonad cells may inhibit female development, thereby inducing the individuals to become males. Thus, our results raise a promising hypothesis that sult1st6y is the sex determination gene in Thunnus fishes or at least functions at a crucial point in the sex-differentiation cascade.